Developing Core/Shell Capsules Based on Hydroxypropyl Methylcellulose and Gelatin Through Electrodynamic Atomization for Betalain Encapsulation - Guarda-Moraga, A; Galotto-Lopez, M; Rojas-Sepulveda, A; Garrido-Ayala, L; Velasquez, E (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Betalains are bioactive compounds with remarkable functional and nutritional activities for health and food preservation and attractiveness. Nevertheless, they are highly sensitive to external factors, such as oxygen presence, light, and high temperatures. Therefore, the search for new structures, polymeric matrices, and efficient methods of encapsulation of these compounds is of great interest to increase their addition to food products. In this work, betalains were extracted from red beetroot. Betacyanin and betaxanthin contents were quantified. Subsequently, these compounds were successfully encapsulated into the core of coaxial electrosprayed capsules composed of hydroxypropyl methylcellulose (HPMC) and gelatin (G). The effect of incorporating the carbohydrate and the protein both in the core or shell structures was studied to elucidate the best composition for betalain protection. Morphological, optical, and structural properties were analyzed to understand the effect of the incorporation of the bioactive compounds in the morphology, color, and chemical interactions between components of resulting electrosprayed capsules. The results of the thermogravimetric and encapsulation efficiency analysis coincided that the incorporation of beetroot extract in G in the core and HPMC in the shell resulted in the structure with greater betalain protection. The effectiveness of the core/shell structure was confirmed for future food applications. © 2023 by the authors.